Transforming surgical care and safety: dissecting the impact of checklists in the global south - Reddy, Chaitanya; Bains, Lovenish; Kumar, Padmavathy Krishna; Zadey, Siddhesh (Frontiers in Surgery, 2025)
Surgical errors and preventable harm remain major public health concerns, especially in the low- and middle-income countries (LMICs). The World Health Organization's Surgical Safety Checklist (SSC) was developed as a low-cost, high-impact tool to improve surgical outcomes and enhance patient safety. This review examines how the SSC functions both as a safeguard against preventable errors and as a driving force for reducing morbidity and mortality in surgical care. Drawing on evidence from LMICs, we examine the checklist's impact on reducing surgical errors, associated complications, morbidity, and mortality, while also fostering better team communication and accountability in operating rooms. Despite SSC's proven benefits, its implementation in LMICs remains inconsistent due to barriers such as hierarchical team dynamics, limited training, infrastructure gaps, and lack of leadership support. The article highlights approach such as including structured training programs, hands-on demonstrations, workshops and the use of digital tools and platforms for better SSC implementation. It also emphasizes the role of local champions, leadership endorsement, local adaptations and regular audits with feedback to sustain adherence and foster a culture of surgical safety. Strengthening these efforts can transform the SSC from a procedural formality into a powerful tool for surgical safety, providing a practical pathway to enhance patient safety and quality in global surgical care.